A Review of Erucic Acid Production in Brassicaceae Oilseeds: Progress and Prospects for the Genetic Engineering of High and Low-Erucic Acid Rapeseeds (Brassica napus) - Wang, Pandi; Xiong, Xiaojuan; Zhang, Xiaobo; Wu, Gang; Liu, Fang (Frontiers in Plant Science, 2022)
Erucic acid (C22:1,ω-9, EA) is a very-long-chain monounsaturated fatty acid that is an important oleochemical product with a wide range of uses in metallurgy, machinery, rubber, the chemical industry, and other fields because of its hydrophobicity and water resistance. EA is not easily digested and absorbed in the human body, and high-EA rapeseed (HEAR) oil often contains glucosinolates. Both glucosinolates and EA are detrimental to health and can lead to disease, which has resulted in strict guidelines by regulatory bodies on maximum EA contents in oils. Increasingly, researchers have attempted to enhance the EA content in oil crops to serve industrial applications while conversely reducing the EA content to ensure food safety. For the production of both LEAR and HEAR, biotechnology is likely to play a fundamental role. Elucidating the metabolic pathways of EA can help inform the improvement of oil crops through transgenic technology. In this paper, we review the biosynthetic pathways of EA, introduce the EA resources from plants, and focus on research related to the genetic engineering of EA in oil crops. In addition, the industrial applications of HEAR oil are briefly described, the effects of the environment on EA production are addressed, and the safe cultivation of HEAR and LEAR is discussed. This paper supports further research into improving fatty acids in oil crops through transgenic technologies and molecular breeding techniques, thereby advancing the commercialization of transgenic products for better application in various fields.